Investigations on orbital forming of sheet metals to manufacture tailored blanks with a defined sheet thickness variation - Plettke, Raoul; Opel, Simon (Advanced Materials Research, 2013)
Orbital forming is an incremental bulk cold forming process with many advantages. It can produce net-shape or near-net-shape parts that have superior mechanical properties due to work hardening compared to manufacturing with cutting processes or hot forming. In this work the orbital forming process is employed in a closed-die configuration. A rising of the material thickness in the outer areas of a circular sheet metal blank is enabled by preventing the lateral material flow. The main effects and subsequently the effects of the interaction of parameters were investigated by a two-step design of experiments. A screening plan was used to identify the statistically relevant parameters. The effects were then studied in a subsequent central-composite design of experiments. With the measured data a nonlinear response-surface model was parameterized to describe the dependency of the mould filling on the investigated process parameters. This model was validated experimentally and showed a good agreement to reality. Additionally a new concept for the tool system was developed and investigated. The form-defining cavity can be changed from the upper punch to the counterpunch. © (2013) Trans Tech Publications, Switzerland.
LFT Import::2019-07-29 (1883)
Keywords: Cold forming; Orbital forming; Steel